Generation to Generation : Life Cycles of the Family Business. - Davis, John A.; Hampton, Marion McCollom; Lansberg, Ivan.; Kelin E., Gersick; Gersick, Kelin E. (Boston : Harvard Business Review Press, 1997)
Generation to Generation presents one of the first comprehensive overviews of family business as a specific organizational form. Focusing on the inevitable maturing of families and their firms over time, the authors reveal the dynamics and challenges family businesses face as they move through their life cycles. The book asks questions, such as: what is the difference between an entrepreneurial start-up and a family business, and how does one become the other? How does the meaning of the business to the family change as adults and children age? How do families move through generational changes.
Print version record.
Added to collection customer.56279.3 - Master record variable field(s) change: 072, 650
Keywords: Family-owned business enterprises -- Management; Family-owned business enterprises -- Succession; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; elektronické knihy; electronic books